Whey protein active films incorporated with a blend of essential oils: Characterization and effectiveness - Ribeiro-Santos, Regiane (2018)
Whey protein concentrate (WPC) films incorporated with a blend of Cinnamomum cassia, Cinnamomum zeylanicum, and Rosmarinus officinalis essential oils were characterized and evaluated for their effectiveness as an antioxidant for food applications. The effect of the incorporation of essential oils (EOs) at different concentrations (1, 2, 2.7, and 5% w/w) in WPC were studied by measuring their physical, optical, mechanical, and microstructural properties, in order to evaluate their behavior as a food packaging. The effectiveness of these active WPC films as a packaged was evaluated using a fatty food model (salami). The state of the salami oxidation was measured by the TBARs and hexanal assays during 180days of storage. A yellowish characteristic color and opacity of WPC-based films tend to increase with the increase of the EO concentration in the film formulation. While films containing 1 and 2% of EOs showed to be the most hydrophobic and present the lowest moisture content and solubility in water, films with higher EOs % (2, 2.7, and 5%, w/w) presented the highest water vapor transmission rate. The developed WPC active films showed to be heterogeneous, presenting cracks and pores due to the weakening of the polymer chain interaction forces by the EOs, which affected their mechanical behavior. WPC films incorporated with EOs may retard lipid oxidation induced by UV light in food. Besides, they showed to be very effective in the reduction of lipid oxidation in a previous assay with salami, with a longer storage time.